2013
DOI: 10.1111/gwat.12044
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Bacteria and Virus‐Like Particle Abundances During Purging of Unconfined Aquifers

Abstract: Standard methodologies for sampling the physicochemical conditions of groundwater recommend purging a bore for three bore volumes to avoid sampling the stagnant water within a bore and instead gain samples representative of the aquifer. However, there are currently no methodological standards addressing the amount of purging required to gain representative biological samples to assess groundwater bacterial and viral abundances. The objective of this study was to examine how bacterial and viral abundances chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 47 publications
2
19
1
Order By: Relevance
“…These counts are consistent with commonly reported microbial cell counts of 10 3 −10 8 cells ml -1 in groundwater [25,4448]. Following the addition of synthetic wastewater, mean bacterial and VLP abundances increased to 10 4 –10 8 cells ml -1 (Fig 5).…”
Section: Discussionsupporting
confidence: 89%
“…These counts are consistent with commonly reported microbial cell counts of 10 3 −10 8 cells ml -1 in groundwater [25,4448]. Following the addition of synthetic wastewater, mean bacterial and VLP abundances increased to 10 4 –10 8 cells ml -1 (Fig 5).…”
Section: Discussionsupporting
confidence: 89%
“…The reasons for these low microbial and viral numbers are yet to be elucidated, but may be linked to the oligotrophic nature of groundwater (Wilhartitz et al, 2013). Data from Australian confined and unconfined aquifers suggest, nonetheless, small-scale heterogeneity in microbial communities, both prokaryotic and viral, which in turn suggests active microbial dynamics rather than inactive homogeneous suspensions of cells (Roudnew et al, 2013(Roudnew et al, , 2014.…”
Section: (C) Aquifersmentioning
confidence: 99%
“…Purging wells is necessary to gain representative biological samples20212526272829 because wells represent an artificial environment that is enriched in oxygen and organic matter, may have some light, and contains a large volume of open water compared to that of the aquifer25. As such, wells often contain higher stygofaunal abundances than aquifers252730.…”
mentioning
confidence: 99%
“…Previous studies have also shown differences in microbial assemblages between well and aquifer samples using community fingerprinting techniques (e.g. TRFLP)27 and flow cytometry28. Whilst such studies have shown differences in the structure and abundance of microbial communities, the lack of taxonomic resolution in these methods means that the implications of purging (or not) on assessments of biological structure and potential ecosystem function in groundwaters have not yet been adequately explored.…”
mentioning
confidence: 99%